Bruce Lee an interview with the Mandarin superstar ([s.l.] : Lumiere Pictures, 1993)
Bruce Lee's most in-depth interview filmed in 1971 as part of the Pierre Berton Show for the Canadian Broadcasting Corporation
Keywords: Lee, Bruce, -- 1940-1973; Motion picture actors and actress -- Hong Kong -- Biography; Martial artists -- Hong Kong -- Biography